The Attitude of Pregnant Women and Health Workers for Influenza Vaccination - N. I. Briko; T. S. Saltykova; A. N. Gerasimov; A. A. Pozdnyakov; E. B. Brusina; L. P. Zueva; A. V. Lyubimova; A. A. Golubkova; T. G. Suranova; T. V. Tolokonnikova; V. B. Turkutyukov; V. I. Shumilov; et al. (Эпидемиология и вакцинопрофилактика)
Influenza and ARVI - the main nosological form in structure of all infectious diseases. Influenza is especially dangerous to pregnant women. Purpose: to estimate commitment of pregnant women and health workers to vaccination against influenza. Materials and methods: form No. 5, form of the statistical account No. 1 - influenza the section 1, information from the official site of Federal State Budgetary Institution Scientific Research Institute of influenza of the Ministry of Health of the Russian Federation; materials of various conferences and the congresses on a influenza problem, information and analytical reference of the Ministry of Health of the Russian Federation. There were asked 1126 pregnant women on various durations of gestation and 447 health workers in various territories of the Russian Federation. Statistical processing was carried out with use of the Microsoft Excel 2010 and IBM SPSS Statistics 20.0 programs. Results and discussion: Among the interviewed pregnant women planned or were already vaccinated against influenza only 8% of women. The most frequent causes of failure from vaccination against influenza during pregnancy: doubt in safety (41.8%), ignorance about possibilities of vaccination (21,1%), lack of need for vaccination (18,7%). Only 25% of respondents knew about entering vaccination against influenza during pregnancy into a national calendar. At the same time only in 15% of health workers suggested pregnant women to be vaccinated from influenza. 73% of the interviewed health workers didn't recommend vaccination against influenza to pregnant women because they consider undesirable an intervention in immunity of the pregnant woman, 33% doubt in safety of vaccination, 13% don't know about a possibility of vaccination of pregnant women at all, 6% have personal negative experience of vaccination, and 4% don't see need for vaccination from influenza. Conclusion: the received materials showed need of development of knowledge at health workers of a vaccinal prevention of infectious diseases, including also vaccination against influenza during pregnancy, and also to carry out broad and active information work with the population, attracting mass media.